The families of affection and their reflections in current society (Research, Society and Development, 2021)
Scientific article carried out in order to study the different forms of families, especially with regard to the search for happiness and the consequent recognition of plural families and outside the archaic standards. Initially, we sought to characterize and define the concept of family and later demonstrate how important State power is and legitimizes the concept of family. For the preparation of this study, all possibilities of family recognition and its legal effects were analyzed. This article also analyzed the principle of affectivity and the different forms of existing family constitutions. We sought to demonstrate that affection is the main link between people when we seek to define what “family” actually is, clearly demonstrating that affection is not a mere vague concept, but a guiding principle. That said, the central theme of this work is to analyze the evolution of the family entity seen from a civil constitutional perspective.